Design Considerations of Solar Water Heating System: A Review - Kuikel, Shraddha; Shah, Malesh; Maharjan, Maulik Man; Khanal, Shuvas; Homagain, Sudeep (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Solar energy is considered as one of the best alternative sources of energy since it is clean and sustainable for the environment. Extensive research on various aspects of solar water heating systems has been done in order to increase the overall efficiency of the system and optimize the design. The size of the system depends on temperature required to the customer, solar radiation, arrangement of the solar system, geographical condition and so on. Hence, it is important to design the SWH system, considering such parameters to assure maximum benefit to the user. This paper exclusively discusses the design aspect of the components of the SWH system. The first part of the paper deals with the summary of different system components that includes collector, storage tank, heat exchanger and coating on pipes. The second part of the paper discusses the advancement in the system in terms of various parameters such as overall efficiency, temperature, flow rate etc. The paper also includes the discussion on the use of simulation tools, numerical modelling and researches in heat transfer components that show prominent technological advancements in SWH systems. In addition to that, the paper comprises ample discussions regarding the use of SWH systems in a developing country like Nepal. Different tracking and data acquisition systems used in the countries having similar climatic, topographic and geopolitical conditioning were studied to draw optimum information on design of the solar system for Nepal. The review shows that a major portion of the SWH system design includes the collector sizing and its design because the overall system efficiency depends majorly on the collector efficiency. The various approaches for improvement in performance and efficiency, and adaptation with the recent advances has helped to enhance and upgrade the design of solar water heating systems.